1991
DOI: 10.1093/carcin/12.6.1079
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic activation of dibenz[a,h]anthracene in mouse skin examined by 32P-postlabelling: minor contribution of the 3,4-diol 1,2-oxides to DNA binding

Abstract: Dibenz[a,h]anthracene (DB[a,h]A) and the related 3,4-diol and anti- and syn-3,4-diol 1,2-oxides were applied to the shaved dorsal skin of groups of four C57Bl/CB1 mice. Twenty-four hours later the mice were killed, DNA isolated from the treated skin, hydrolysed and examined for the presence of aromatic adducts using the nuclease P1 modification of the 32P-postlabelling technique. Autoradiography of the maps obtained by chromatography on polyethyleneimine-cellulose plates showed that six DNA adduct spots that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…This symmetrical compound can form not only the bay-region 3,4-diol-1,2-epoxide, but also the 3,4:10,11-bis-diol-1,2-epoxide (Carmichael et al, 1993; Fuchs et al, 1993a, 1993b). When the metabolism, mutagenicity, carcinogenicity and formation of DNA adducts of this compound were studied, all of the results indicated that it is activated via the diol epoxide pathway (Fuchs et al, 1993a, 1993b; Lecoq et al, 1991, 1992; Platt, et al, 1990). One study suggests that the 3,4:10,11-bis-diol-1,2-epoxide is the most important for the carcinogenicity of this compound (Carmichael et al, 1993).…”
Section: Ultimate Carcinogenic Metabolites Of Aromatic Hydrocarbonsmentioning
confidence: 99%
“…This symmetrical compound can form not only the bay-region 3,4-diol-1,2-epoxide, but also the 3,4:10,11-bis-diol-1,2-epoxide (Carmichael et al, 1993; Fuchs et al, 1993a, 1993b). When the metabolism, mutagenicity, carcinogenicity and formation of DNA adducts of this compound were studied, all of the results indicated that it is activated via the diol epoxide pathway (Fuchs et al, 1993a, 1993b; Lecoq et al, 1991, 1992; Platt, et al, 1990). One study suggests that the 3,4:10,11-bis-diol-1,2-epoxide is the most important for the carcinogenicity of this compound (Carmichael et al, 1993).…”
Section: Ultimate Carcinogenic Metabolites Of Aromatic Hydrocarbonsmentioning
confidence: 99%
“…Thus the postulated reactivity of the ultimate mutagens of the three bisdihydrodiols was confirmed by the extent of DNA binding in mouse skin (42), which rose from no detectable binding in the case of DBA-3,4:12,13-bisdihydrodiol to weak binding in the case of DBA-3,4:8,9-bisdihydrodiol, reaching its highest value in the case of DBA-3,4:10,11bisdihydrodiol. Furthermore, DBA and DBA-3,4-dihydrodiol yielded the same pattern of DNA adducts when incubated with rat liver microsomes (38,39) or when applied to mouse skin in vivo (40), demonstrating anew the biological significance of the M-region dihydrodiol of DBA as precursor of its genotoxic metabolite(s). In both metabolizing systems DNA adducts based on bay-region dihydrodiol oxides were detected (38)(39)(40) and could be characterized ( 39), yet, especially in vivo, their amount was surpassed by more polar adducts (40).…”
Section: Resultsmentioning
confidence: 73%
“…Furthermore, DBA and DBA-3,4-dihydrodiol yielded the same pattern of DNA adducts when incubated with rat liver microsomes (38,39) or when applied to mouse skin in vivo (40), demonstrating anew the biological significance of the M-region dihydrodiol of DBA as precursor of its genotoxic metabolite(s). In both metabolizing systems DNA adducts based on bay-region dihydrodiol oxides were detected (38)(39)(40) and could be characterized ( 39), yet, especially in vivo, their amount was surpassed by more polar adducts (40). Remarkably, this could be shown not only with mouse skin (40) but also with human skin in culture (41).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Una variedad de métodos físicos fueron descriptos para la detección de aductos, incluyendo espectroscopia de fluorescencia de línea angosta (fluorescence line narrowing spectroscopy), espectroscopia de fluorescencia sincrónica (synchronous fluorescence spectroscopy) y algunos procedimientos especializados de cromatografía gaseosaespectrometría de masa (CG-EM) (Weston, 1993). Los métodos físicos combinan alta sensibilidad sin requerir una anterior radiomarcación de los carcinógenos o de sus aductos, y pueden ser no-destructivos (Lecoq et al, 1991(Lecoq et al, , 1992Carmichael et al, 1993;Nesnow et al, 1994;Hecht et al, 1995).…”
Section: Métodos Analíticosunclassified